2020
DOI: 10.3390/antiox9101021
|View full text |Cite
|
Sign up to set email alerts
|

The Selenoprotein MsrB1 Instructs Dendritic Cells to Induce T-Helper 1 Immune Responses

Abstract: Immune activation associates with the intracellular generation of reactive oxygen species(ROS). To elicit effective immune responses, ROS levels must be balanced. Emerging evidenceshows that ROS‐mediated signal transduction can be regulated by selenoproteins such asmethionine sulfoxide reductase B1 (MsrB1). However, how the selenoprotein shapes immunityremains poorly understood. Here, we demonstrated that MsrB1 plays a crucial role in the ability ofdendritic cells (DCs) to provide the antigen presentation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Previous studies have indicated that selenium influences production of B cells and their resident antibodies, as well as the differentiation of T cells and macrophages across multiple species [ 19 22 ]. It has been suggested that the differentiation and immune function of chicken DCs can also be influenced by selenium [ 23 , 24 ]; moreover, high levels of organoselenium drugs like ebselen have been shown to inhibit DC-induced proliferation of T cells and secretion of cytokines [ 4 ]. In this study, human imDCs were exposed to different dosages of Na 2 SeO 3 and findings revealed that those below 0.1 μmol/L were capable of promoting proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that selenium influences production of B cells and their resident antibodies, as well as the differentiation of T cells and macrophages across multiple species [ 19 22 ]. It has been suggested that the differentiation and immune function of chicken DCs can also be influenced by selenium [ 23 , 24 ]; moreover, high levels of organoselenium drugs like ebselen have been shown to inhibit DC-induced proliferation of T cells and secretion of cytokines [ 4 ]. In this study, human imDCs were exposed to different dosages of Na 2 SeO 3 and findings revealed that those below 0.1 μmol/L were capable of promoting proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies have indicated that both mitochondrial reactive oxygen species (ROS) and superoxide anions (O 2 − ) contribute to the development of DCs. For example, investigations in mice have reported that ROS activates DCs and promotes interaction between DCs and T cells during antigen presentation [ 4 ], as well as induces apoptosis or necrosis of DCs via Acinetobacter baumannii outer membrane protein A [ 5 ]. Among humans, ROS stimulates differentiation of mononuclear cells into DCs [ 6 ], and O 2 − assists in the maturation of imDCs into mDCs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein oxidative modification state is regulated by balance between ROS and methionine sulfoxide reductase (Mrs). Mrsb1 deficiency in DC delays its maturation and decreases DC-induced Th1 differentiation, and is associated with defective differentiation of follicular helper T cell cells in vivo (81). Transforming growth factor β (TGF-β) is a cytokine with broad regulatory functions in T cell development and differentiation.…”
Section: The Effects Of Ros On T Helper 1/t Helper 2 and T Helper 17/mentioning
confidence: 99%
“…Previous studies on Msr have mainly focused on its role in resistance to oxidative stress in organisms [ 21 , 22 , 23 , 24 ], which is related to repair of oxidized proteins, such as GroEL [ 25 ], Fth [ 26 ], hERG [ 27 ], apolipoprotein A-I [ 28 ], CaMKII [ 29 ], TRPM6 channel [ 30 ], HypT [ 31 ], actin [ 32 ], CaM [ 33 , 34 ], GrpEL1/Mge1 [ 35 ], heme oxygenase [ 36 ], and high-density lipoprotein [ 37 ]. Growing evidence suggests that Msr may be implicated in the regulation of protein function by modifying the sulfoxidation of proteins in a similar manner to that of other protein modification, such as phosphorylation [ 38 , 39 , 40 , 41 ]. However, only a few potential targets of Msr in relation to sulfoxidation modification have been investigated in higher plants [ 23 , 34 , 42 ].…”
Section: Introductionmentioning
confidence: 99%